ANALISIS FAKTOR RISIKO KEJADIAN STROKE PADA KELOMPOK USIA ≥35 TAHUN DI SULAWESI UTARA (ANALISIS DATA RISKESDAS 2018) - Lia Mulyani (2023)
Stroke is a major health issue that ranks as the second-leading cause of disability and death worldwide. Around 12.2 million people worldwide experience stroke, and 6.5 million of them die each year. The prevalence of stroke has been increasing in Indonesia, including the province of North Sulawesi. This study aims to analyze the risk factors for stroke incidence in North Sulawesi among individuals aged 35 years and over based on the Riskesdas 2018 data. This quantitative study adopts a cross-sectional design with an analytical observational approach. The data analysis involves chi-square tests and multiple logistic regressions with 7111 respondents. The results of the multivariate analysis show that hypertension (p=0.000; AOR 8.739; 95% CI 5.758-13.263), physical activity (p=0.000; AOR 2.771; 95% CI 1.944-3.948), gender (p=0.000; AOR 2.047; 95% CI 1.388-3.117), heart disease (p=0.015; AOR 1.919; 95% CI 1.133-3.250), age (p=0.008; AOR 1.669; 95% CI 1.144-2.434), occupation (p=1.693; 95% CI 1.145-2.504), and high-fat diet (p=0.603; 95% CI 0.390-0.932) are significantly associated with stroke incidence in the study. In conclusion, hypertension is the leading risk factor for stroke incidence among individuals aged ≥35 years in North Sulawesi. Keywords: Risk factors, Hypertension, Stroke, North Sulawesi.